CONTENT ANALYSIS OF THE ADDRESSES OF THE PRESIDENT OF THE REPUBLIC OF KAZAKHSTAN BETWEEN STRATEGY-2030 AND STRATEGY-2050 - SMAGULOV, Kadyrzhan; SANTAEVA, Kulimkoz; BULANOV, Erzhan (CENTRAL ASIA AND THE CAUCASUS, 2017)
The authors conducted a quantitative content analysis of the Addresses of the President of the Republic of Kazakhstan delivered between the adoption of Strategy-2030 (1997) and Strategy-2050 (2012). Their research was based on analyzing fifteen Presidential Addresses to identify the political priorities of the state. The study concluded that, under the same President, the strategic priorities of state policies have remained consistent regardless of internal and external contexts. Additionally, it found that the President has been and continues to be the primary initiator of reforms and modernization in the political, social, and economic areas. This indicates that the governance structure in Kazakhstan can be characterized as super-presidential.Here we will analyze the annual Addresses of the President of the Republic of Kazakhstan, Nursultan Nazarbayev, delivered between 1998 and 2012, during the periods when Strategy-2030 and Strategy-2050 were being adopted. It is crucial to trace the priorities of the country’s development and observe how they evolved from one Address to another. This analysis is particularly interesting because all the Addresses were delivered by the same President, which allows us to study the dynamics of the country’s state policies over these fifteen years.We employed several scholarly methods for this analysis, including content analysis, historical and comparative analysis, and a systemic approach. The primary method used was quantitative content analysis of frequently mentioned words in the Addresses of the President of the Republic of Kazakhstan, Nursultan Nazarbayev, delivered between 1998 and 2012.The Addresses selected for research were those delivered annually during this period. To analyze the quantitative index of nouns, adjectives, and derivatives of certain pronouns, we utilized the QDA Miner and WordStat programs, focusing on their functional utilities. Keywords with similar meanings were grouped together.Our analysis was restricted to words or groups of words that appeared in all the studied annual Presidential Addresses at least 45 times, with each word being mentioned no fewer than three times on average in any of the Addresses.